RESULTS OF EXPERIMENTS OF STUDYING THE COMPOSITION AND PURIFICATION OF TECHNICAL WATERS - Khurmamatov, A (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article presents the results of a study to determine the elementary composition of technical water formed by the gas processing plant. Some defined elements from the composition of process technical water include: Al, As, Ba, Bi, Ca, Cd, Co, Tl, Cr, Cu, Fe, In, K, Li, Mg, Zn, Mn, Mo, Na, Ni, Pb, Sb, Sr. Determination of the elementary composition of technical water is carried out by using the device ICPE-9000 Shimadzu. Moreover, the results of reducing the hardness of technical water are also presented and the most suitable reagent is determined. In order to reduce the hardness of technical water, reagents Ca(OH)2, Na(PO4)3, Na3PO4, Al2(SO4)3, Sulfonyl, Na(PO3)n, H2O, NaF, Al2(SO4)3, 18H2O, were used in the experiments.